Repair plastic surgery in patients with breast cancer - A. A. Volchenko; D. D. Pak; F. N. Usov (ABV-press, 2014)
The paper considers a role of repair plastic surgery in the treatment of patients with breast cancer (BC). It describes the cur rent surgical BC treatment strategy aimed at fulfilling two tasks: to ensure a reliable cancer cure and to create favorable conditions for breas t repair. There is evidence that there is no association between the prognosis of BC and the performance of repair plastic operations. It is concluded that plastic surgery heads the list of rehabilitation measures for BC today.